Kepemimpinan Kepala Sekolah, Komitmen Guru, dan Kepuasan Kerja Guru dalam Meningkatkan Produktivitas Guru di SD Kristen BPK Penabur Indramayu - Veronika Irawan; Hery Winoto Tj (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
High teacher productivity will certainly have a positive impact on a school. Teachers at the elementary school level (SD) have a very important role in developing students' basic skills. This study aims to analyze the leadership of the principal, teacher commitment, and teacher job satisfaction in improving teacher productivity. This study uses a qualitative approach with a case study type. The case study was chosen because it allows researchers to explore in depth the phenomenon of principal leadership, teacher commitment, and teacher job satisfaction in improving teacher productivity at SD KRISTEN BPK PENABUR Indramayu. The subjects of this study are teachers at SD KRISTEN BPK PENABUR Indramayu. Teachers who have varying work experiences will be important subjects in this study. They will provide perspectives on principal leadership, work commitment, job satisfaction levels, and factors that influence their productivity in teaching and carrying out professional duties. Data collection techniques used in this study include in-depth interviews, observation, and documentation studies. The data analysis process is carried out systematically through several stages, namely data reduction, data presentation, drawing conclusions, and verification. This study employed several techniques to ensure data validity, including source triangulation, technical triangulation, peer review, and member checking. The results indicate that transformational principal leadership plays a significant role in enhancing teacher commitment and job satisfaction, which ultimately impacts teacher productivity. High teacher commitment results from supportive leadership, appreciation, and a sense of belonging to the school. Teacher job satisfaction is influenced by a positive work environment, positive relationships between colleagues, and the principal's attention to teacher welfare and professional development. Effective principal leadership, high teacher commitment, and teacher job satisfaction contribute to increased teacher productivity.